Forming free and ultralow-power erase operation in atomically crystal TiO2 resistive switching. (1st February 2017) - Dai, Yawei; Bao, Wenzhong; Hu, Linfeng; Liu, Chunsen; Yan, Xiao; Chen, Lin; Sun, Qingqing; Ding, Shijin; Zhou, Peng; Zhang, David Wei
Abstract: Two-dimensional layered materials (2DLMs) have attracted broad interest from fundamental sciences to industrial applications. Their applications in memory devices have been demonstrated, yet much still remains to explore optimal materials and device structure for practical application. In this work, a forming-free, bipolar resistive switching behavior are demonstrated in 2D TiO2 -based resistive random access memory (RRAM). Physical adsorption method is adopted to achieve high quality, continuous 2D TiO2 network efficiently. The 2D TiO2 RRAM devices exhibit superior properties such as fast switching capability (20 ns of erase operation) and extremely low erase energy consumption (0.16 fJ). Furthermore, the resistive switching mechanism is attributed to the formation and rupture of oxygen vacancies-based percolation path in 2D TiO2 crystals. Our results pave the way for the implementation of high performance 2DLMs-based RRAM in the next generation non-volatile memory (NVM) application.